2021
DOI: 10.3390/jpm11050345
|View full text |Cite
|
Sign up to set email alerts
|

Drug Response Diversity: A Hidden Bacterium?

Abstract: Interindividual heterogeneity in response to treatment is a real public health problem. It is a factor that can be responsible not only for ineffectiveness or fatal toxicity but also for hospitalization due to iatrogenic effects, thus increasing the cost of patient care. Several research teams have been interested in what may be at the origin of these phenomena, particularly at the genetic level and the basal activity of organs dedicated to the inactivation and elimination of drug molecules. Today, a new branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 98 publications
1
4
0
Order By: Relevance
“…In contrast to reduced microbial community abundance in 7-week-old db/db mice, the alpha diversity analyses demonstrated that neither microbiota richness nor uniformity changed in the colon and small intestine of any group which is consistent with some clinical reports that diabetes is not associated with alpha diversity indices (Chao 1, Shannon and Simpson) [17]. In diabetic animal models with long-term hyperglycemia, abundances of the bacterial genera Helicobacter and Alistipes are increased [29,30], while those of Tyzzerella, Lachnoclostridium, Anaerotruncus, Roseburia, Bacteroides, Parabacteroides, and Lactobacillus are decreased [31][32][33][34][35]. We did not observe any change in the colonic abundance of these bacteria during early-stage hyperglycemia (7-week-old), although body weight and blood glucose levels increased from 5 weeks age [13].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast to reduced microbial community abundance in 7-week-old db/db mice, the alpha diversity analyses demonstrated that neither microbiota richness nor uniformity changed in the colon and small intestine of any group which is consistent with some clinical reports that diabetes is not associated with alpha diversity indices (Chao 1, Shannon and Simpson) [17]. In diabetic animal models with long-term hyperglycemia, abundances of the bacterial genera Helicobacter and Alistipes are increased [29,30], while those of Tyzzerella, Lachnoclostridium, Anaerotruncus, Roseburia, Bacteroides, Parabacteroides, and Lactobacillus are decreased [31][32][33][34][35]. We did not observe any change in the colonic abundance of these bacteria during early-stage hyperglycemia (7-week-old), although body weight and blood glucose levels increased from 5 weeks age [13].…”
Section: Discussionsupporting
confidence: 87%
“…The effect of metformin on the gut microbiota has been widely studied in both patients and animal models. Metformin increases the abundance of colonic bacteria (e.g., Prevotellaceae_UCG-001, Roseburia, Lactobacillus and Rikenellaceae_RC9_gut_group) in diabetic and some digestive tract diseases while decreasing Helicobacter abundance [29,32,35,37]. Additionally, metformin increases Lactobacillus abundance and decreases Bacteroides abundance in the small intestine [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Drugs affect the diversity and richness of microbiota, and microbiota also affects the pharmacology and efficacy of drugs. Pharmacomicrobiomics is an emerging field that detects the effect of microbiome alterations on drug pharmacokinetics ( ElRakaiby et al, 2014 ; Aziz et al, 2018 ; Doestzada et al, 2018 ; Panebianco et al, 2018 ; Rowland et al, 2018 ; Hannachi and Camoin-Jau, 2021 ). Previous researches suggest that intestinal microbiota had a strong modification effect on the metabolic process of drugs, but the influence of intestinal microbiota changes on drug disposition in vivo remains to be further studied ( Zimmermann et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific community, the study of how microorganisms influence drug response has been of increasing interest in recent years. Since 2010, when the term "pharmacomicrobiomics" was coined to describe the effects of the microbiome on drug absorption, activity and toxicity, numerous research studies have been conducted on this topic [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The microbiome, and even dysbiosis, specifically refer to symbiotic or commensal microorganisms. It is worth mentioning that, in this context, pharmacomicrobiomics does not provide a specific definition for interactions between drugs and pathogenic microorganisms, because an infection is characterized by the invasion and proliferation of pathogenic microorganisms in body tissues [9,17,18]. As far as we know, there is no specific term like "pharmaco-infection interaction" in the current literature.…”
Section: Introductionmentioning
confidence: 99%